Analisis Penerapan E-Government Dalam Pelayanan Administrasi Kependudukan di Kabupaten Bone - Mayestika Fortuna Jaharuddin (Departemen Ilmu Pemerintahan Fisip Unhas, 2024)
IKD or Identitas Kependudukan Digital is electronic information used to represent population documents and return data in digital applications via mobile phones. This study aims to determine the utilization of the Identitas Kependudukan Digital (IKD) application in administering the Residence Identification Card in Bone Regency. This study used descriptive qualitative research methods. The data collection techniques used were observation, interviews, and documentation. The location of this study was at the Civil Registry Service Office of Bone Regency. The result of this study indicate that the utilization of the IKD can be measuring using indicators of implementation of E-Government in public services, such as (1) efficiency, the utilization of IKD in Bone Regency runs efficiently, as proven by the use of IKD that makes it easier for the public to use the Identification Card; (2) effectiveness, IKD services in Bone Regency have been realized quite well as proven by the use of IKD that is very effective and practical as it can be used anywhere and anytime; and (3) transparency, publication of IKD services products makes it easy for the public to follow, monitor, and control the development of services provided using the IKD application.